Formability and fracture in deep drawing sheet metals: Extended studies for pre-strained anisotropic thin sheets. (15th March 2020) - Basak, Shamik; Panda, Sushanta Kumar; Lee, Myoung-Gyu
Highlights: LDR and fracture cup height was experimentally evaluated for different sheet materials. Necking and fracture limits were theoretically estimated using MK and BW model. LDR, thinning profile estimated using MK model incorporating anisotropy yield theory. Anisotropic BW curve was used into GISSMO platform to predict fracture cup height. PEPS based failure limits used to identify necking and fracture of pre-strained sheet. Abstract: In this study, experimental and numerical investigations were conducted to predict the formability and fracture behavior of as-received and pre-strained sheet materials during deep drawing process. In this context, various laboratory scale experimental setups were developed to impart different types and amounts of pre-strain such as 5% and 10% equi-biaxial pre-strains (5% EBP and 10% EBP), 10% plane strain pre-strain (10% PSP), and 10% uni-axial pre-strain (10% UP) on the extra deep drawing (EDD) steel and aluminum alloy (AA5052) sheets of 1.2 mm thickness. Further, all the pre-strained sheet samples were deformed using a cylindrical deep drawing setup. The forming limit diagrams (FLDs) of as-received sheets were predicted by the Marciniak–Kuczyński (MK) model incorporating different anisotropic yield functions such as Hill48 models identified based on r -values (Hill48- r ), and yield stresses (Hill48-σ), and the non-quadratic plane stress Yld2000-2d model. Also, the Bao–Wierzbicki (BW) fracture curve was calibrated using different anisotropic yield functions. Subsequently, the formability in terms of limiting drawing ratio (LDR) was predicted using the MK-FLD. The BW fracture curve was incorporated into the generalized incremental stress state dependent damage model (GISSMO) platform in LS-Dyna software and the fracture behavior was predicted in terms of failure location and cup height at the onset of fracture. It was also found that the incorporation of Barlat Yld2000-2d yield function into the FE simulation efficiently predicted the necking and fracture behavior of as-received sheets. Furthermore, the concept of path independent polar effective plastic strain (PEPS) based failure model was used to predict LDR, thinning profile and fracture cup height of all the different pre-strained sheets. Finally, the strain paths and experimental fracture strains were plotted in 3D fracture locus to get insight into the deformation behavior during the deep drawing experiments. Graphical abstract: Image, graphical abstract